SCIENTIFIC AND THEORITICAL FEATURES OF MARKETING TERMINOLOGY. - Jahonova Umida Jamolovna; Haydarova Kamola Davranovna (TADQIQOTLAR.UZ, 2024)
Annotation: Marketing, often seen as a creative discipline, is actually rooted in solid scientific and theoretical foundations.This article analyzes the scientific and theoritical basis of marketing terminology.Marketing terminology encompasses a wide array of concepts that bridge theoretical frameworks and practical applications in the field of marketing. Understanding these terms is essential for both scholars and practitioners to effectively communicate, analyze, and implement marketing strategies. Below are some theoretical and scientific features of marketing terminology.